2016
DOI: 10.1002/ijc.30150
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale mapping of 8q24 locus identifies multiple independent risk variants for breast cancer

Abstract: Previous genome-wide association studies among women of European ancestry identified two independent breast cancer susceptibility loci represented by single nucleotide polymorphisms (SNPs) rs13281615 and rs11780156 at 8q24. We conducted a fine-mapping study across 2.06 Mb (chr8:127,561,724 −129,624,067, hg19) in 55,540 breast cancer cases and 51,168 controls within the Breast Cancer Association Consortium. We found three additional independent association signals in women of European ancestry, represented by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…The fine‐mapped variants in our study are common polymorphisms (MAF 18%). A higher sample size might have enabled the identification of low frequency putative causal variants within the susceptibility locus to gain additional biological insights . Due to the challenges in the functional characterization of the fine‐mapped loci, only a limited number of breast cancer studies successfully identified the target genes ( FGFR2 , CCND1 , MAP3K1 , TERT , IGFBP5 , TET2 , STXBP4 ) with role in breast cancer etiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fine‐mapped variants in our study are common polymorphisms (MAF 18%). A higher sample size might have enabled the identification of low frequency putative causal variants within the susceptibility locus to gain additional biological insights . Due to the challenges in the functional characterization of the fine‐mapped loci, only a limited number of breast cancer studies successfully identified the target genes ( FGFR2 , CCND1 , MAP3K1 , TERT , IGFBP5 , TET2 , STXBP4 ) with role in breast cancer etiology.…”
Section: Discussionmentioning
confidence: 99%
“…While fine‐mapping approaches are well described in the literature, it is challenging to elucidate the functional relevance of GWAS SNPs, which are predominantly from noncoding regions conferring potential gene regulatory roles. Thus far, 15 breast cancer associated GWAS variants have been fine‐mapped and characterized for putative biological roles …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve SNP density, imputation of the respective regions was performed using the March 2012 release of the 1000 Genomes as reference panel. The functional follow‐up work was not carried out centrally for all regions but divided between the different working groups of BCAC and thus the methods used varied somewhat . In addition, imputed genotypes for 15 new susceptibility loci identified through a meta‐analysis of 11 GWAS with genotypes SNPs generated by imputation using the 1000 Genomes Project March 2012 release as the reference panel were used .…”
Section: Methodsmentioning
confidence: 99%
“…The functional follow-up work was not carried out centrally for all regions but divided between the different working groups of BCAC and thus the methods used varied somewhat. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] In addition, imputed genotypes for 15 new susceptibility loci identified through a meta-analysis of 11 GWAS with genotypes SNPs generated by imputation using the 1000 Genomes Project March 2012 release as the reference panel were used. 5 A list of the 70 SNPs included in the analyses for this report can be found in Supporting Information Table S2.…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%